Has the transition to digital education accelerated due to the pandemic? - Mullaeva, Sohiba (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The coronavirus pandemic has affected the education system as well as all sectors: kindergartens, schools and higher educationinstitutions have been closed en masse. According to UNESCO, 1.7 billion students worldwide today are deprived of offline education due to the suspension of classes. The closure of universities in more than 100 countries has left 90 percent of the world’s students sitting at home